Enterprise risk management : from incentives to controls - Lam, James (Wiley, 2014)
A fully revised second edition focused on the best practices of enterprise risk management Since the first edition of Enterprise Risk Management: From Incentives to Controls was published a decade ago, much has changed in the worlds of business and finance. That's why James Lam has returned with a new edition of this essential guide. Written to reflect today's dynamic market conditions, the Second Edition of Enterprise Risk Management: From Incentives to Controls clearly puts this discipline in perspective. Engaging and informative, it skillfully examines both. - Resumé vydavatel
Risk management requirements.
Keywords: rizikový management; podnikatelská rizika; risk management; business risk; příručky; elektronické knihy; handbooks and manuals; electronic books